Trends and characteristics of infection-related hospital admissions in multiple sclerosis patients in Southwest Finland in 2009–2018 - Anna-Leena Pirttisalo; Jussi O.T. Sipilä; Matias Viitala; Merja Soilu-Hänninen (Elsevier B.V., 2025)
Background
Multiple sclerosis (MS) patients are at increased risk for infections. The aim of this study was to investigate the trends in hospital admissions of patients with MS and to identify the factors predisposing to infection-related admissions.
Methods
Hospital admissions with MS as a primary or an auxiliary diagnosis in the hospital district of Southwest Finland in 2009–2018 were searched and MS patients with infection admissions compared with other MS patients in the hospital district. Data were derived from hospital registries, patient charts and the Finnish MS register. Group comparisons were performed using Pearson´s chi-squared test, Fisher´s exact test or Wilcoxon rank sum test. Overdispersion-adjusted Poisson regression was used to analyze the annual admission numbers and multivariable logistic regression to examine the predictors of infection-related admissions.
Results
1380 hospital admissions for 532 patients were identified. The annual number of admissions decreased by 8.9% annually (p<0.001). Proportion of infection-related admissions declined from 26.5% to 19.5% (p = 0.049). The patients with infection admissions were on average 8.2 years older (p<0.001), more often male (p<0.001), had on average 5.3 years longer disease duration (p<0.001), more disability (median EDSS 5.0 vs. 2.0; p<0.001), more often progressive disease (p<0.001) and more comorbidities (p = 0.006) than other MS patients. Disease modifying therapies (DMTs) were used less often by patients with infection admissions (p<0.001). Infection admissions were not associated with the number of recent relapses. In-hospital mortality was higher in the infection-related admissions (3.57% vs 0.29%; p<0.001). Only 14.3% of patients with over two infection admissions had a DMT during the study period.
Conclusion
Hospital admissions, with or without an infection, have become more infrequent in MS patients of Southwest Finland over the decade from 2009 to 2018. Infection-related admissions were associated with lesser use of DMTs, older age, male gender and disability.